An internal ribosome entry site in the 5′ untranslated region of epidermal growth factor receptor allows hypoxic expression - Webb, Thomas E.; Hughes, A.; Smalley, D.S.; Spriggs, Keith (Nature Publishing Group, 2015)
The expression of epidermal growth factor receptor (EGFR/ERBB1/HER1) is implicated in the progress of numerous cancers, a feature that has been exploited in the development of EGFR antibodies and EGFR tyrosine kinase inhibitors as anti-cancer drugs. However, EGFR also has important normal cellular functions, leading to serious side effects when EGFR is inhibited. One damaging characteristic of many oncogenes is the ability to be expressed in the hypoxic conditions associated with the tumour interior. It has previously been demonstrated that expression of EGFR is maintained in hypoxic conditions via an unknown mechanism of translational control, despite global translation rates generally being attenuated under hypoxic conditions. In this report, we demonstrate that the human EGFR 5′ untranslated region (UTR) sequence can initiate the expression of a downstream open reading frame via an internal ribosome entry site (IRES). We show that this effect is not due to either cryptic promoter activity or splicing events. We have investigated the requirement of the EGFR IRES for eukaryotic initiation factor 4A (eIF4A), which is an RNA helicase responsible for processing RNA secondary structure as part of translation initiation. Treatment with hippuristanol (a potent inhibitor of eIF4A) caused a decrease in EGFR 5′ UTR-driven reporter activity and also a reduction in EGFR protein level. Importantly, we show that expression of a reporter gene under the control of the EGFR IRES is maintained under hypoxic conditions despite a fall in global translation rates.